Unveiling Geographical Variation and Chemotypes of Cupressus torulosa Needle Essential Oil: A Novel Approach Using t‐SNE and HCA - Bhalla, Piyush; Chauhan, Kiran; Varshney, V. K. (Flavour and fragrance journal, 2025)
ABSTRACT This study aimed to assess the geographical variation in the content and chemical composition of Cupressus torulosa needles essential oil across different locations in the Himalayan region of India. The methodology involved the collection of needles from 14 distinct locations, followed by hydro‐distillation using a Clevenger‐type apparatus. Qualitative analysis was conducted using gas chromatography–mass spectrometry (GC–MS), while gas chromatography with flame ionisation detector (GC‐FID) was employed for quantitative analysis. The GC–MS analysis identified a total of 57 compounds, with oxygenated monoterpenes and monoterpene hydrocarbons being the dominant chemical constituents, ranging from 22.5% to 63.01% and from 10.39% to 63.95%, respectively. Terpinen‐4‐ol emerged as the major compound, with concentrations ranging from 101.2 ± 45.7 μg/mg to 393.8 ± 12.5 μg/mg across different locations, with the highest concentration observed in the Dehradun location. The application of t‐distributed stochastic neighbour embedding (t‐SNE) analysis and hierarchical cluster analysis (HCA) revealed the presence of five distinct chemotypes within the essential oil, characterised by different combinations of chemical constituents. These chemotypes were identified as terpinen‐4‐ol/limonene, terpinen‐4‐ol/sabinene, terpinen‐4‐ol, terpinen‐4‐ol/umbellulone, and terpinen‐4‐ol/totarol chemotypes. This research serves as a foundational framework for future investigations aimed at harnessing the unique properties of different chemotypes for specific purposes, potentially facilitating the successful commercialization and utilisation of C. torulosa needles essential oil. This study analysed Cupressus torulosa needles' essential oil from 14 Himalayan locations, identifying 57 compounds with significant variation in chemical composition. Five distinct chemotypes were identified, primarily featuring terpinen‐4‐ol. The research provides a foundation for commercial and therapeutic applications of these unique chemotypes.